How will Labor Markets Adjust to the Crisis? A Dynamic View - Maloney, William (World Bank, Washington, DC, 2012)
Tracking flows of workers among different sectors of employment during economic downturns can shed light on the mechanism of labor market adjustment and inform the design of safety net programs. Though patterns may differ across recessions, the author find that the generally countercyclical rise in unemployment and informality is driven primarily by a reduction in hiring in the formal sector, rather than increased labor shedding. Further, changes in the rate of separations from informality are the largest determinant of changes in unemployment. Both suggest that safety nets should focus less on formal job loss per se and more generally on movements in family incomes, perhaps revealed through self targeting mechanisms.